2010
DOI: 10.1097/ftd.0b013e3181f88f70
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Infant Dose Through Milk in a Lactating Woman Taking Amisulpride and Desvenlafaxine for Treatment-Resistant Depression

Abstract: This study presents the case of a 35-year-old breastfeeding mother who delivered her fourth child 5 months previously and was prescribed 100 mg amisulpride twice daily and 250 mg desvenlafaxine in the morning for treatment-resistant depression. Arriving at this regimen took approximately 2 months postbirth. Because she was keen to continue breastfeeding her infant, and published data on the use of amisulpride and desvenlafaxine were very limited, the clinical team sought assistance from the therapeutic drug mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…1 The available 2 case reports did not suggest any adverse events in the breastfed infants exposed to amisulpride at 250-400 mg/d, despite high RID values of 10.7%-19.5%. 5,6 Although it may be expected adverse events, especially extrapyramidal symptoms in an infant exposed to haloperidol + amisulpride, this expectation did not occur in the current case. Usage at low to moderate doses of these antipsychotics may explain this consequence.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…1 The available 2 case reports did not suggest any adverse events in the breastfed infants exposed to amisulpride at 250-400 mg/d, despite high RID values of 10.7%-19.5%. 5,6 Although it may be expected adverse events, especially extrapyramidal symptoms in an infant exposed to haloperidol + amisulpride, this expectation did not occur in the current case. Usage at low to moderate doses of these antipsychotics may explain this consequence.…”
Section: Discussioncontrasting
confidence: 70%
“…1,3 Reports regarding haloperidol and amisulpride have been less frequently published in the literature. 1,[4][5][6] Almost all of the available reports examining effects of antipsychotics on breastfed infants included usage of only 1 antipsychotic drug, although some authors reported results in the infants exposed to a combination between antidepressants, benzodiazepines, and antipsychotics. [5][6][7] It is unclear whether combined antipsychotics have negative effects on the breastfed infants.…”
Section: Introductionmentioning
confidence: 97%
“…Results must be interpreted with caution as the relative infant dose only estimates the infant's exposure to the drug in milk and does not take the bioavailability of rivaroxaban in the infant into consideration. 7 Moreover, different developmental stages of breastfed infants may influence a drug's pharmacokinetics and thus the exposure to an ingested drug, 8 and potential age-related differences in the pharmacodynamic effects of rivaroxaban in neonates need to be considered. 9 To characterize the infant's exposure precisely, an assay of a drug in blood or urine samples of the breastfed infant would be required.…”
Section: Discussionmentioning
confidence: 99%
“…8 Based on case reports involving the oral formulation, amisulpride is excreted in breast milk. 8,[21][22][23] In women receiving 200 to 400 mg daily, exposure to the infant was estimated at 5% to 11% of the dose, and no adverse or developmental effects were discovered. According to the manufacturer, breastfeeding can be interrupted, and breast milk can be discarded 48 hours after infusion to prevent exposure to the infant.…”
Section: Dosage and Administrationmentioning
confidence: 99%